Phytosociological characteristic of the plant communities with the occurrence of endemic species Cyclamen fatrense - Kanka, Róbert; Turis, Peter; Chilová, Viktória (Hacquetia, 2015)
In this contribution we bring together the basic phytosociological characteristics of communities with the presence of species Cyclamen fatrense in the herb layer. The analysis was made on the basis of 30 original phytosociological relevés. The main criterion for the relevés recording was the selection of the broadest possible range of biotopes with presence and the highest possible abundance of species Cyclamen fatrense on the entire area of its occurrence, which is represented by the Veľká Fatra and Starohorské vrchy Mts. The forest phytocoenoses of the association Carici albae-Fagetum Moor 1952, and phytocoenoses of clearings of the association Epilobio-Atropetum bella-donnae R. Tx. 1931 em. 1950, were classified by using Zürich-Montpellier School method. Additionally, 18 relevés with the presence of species Cyclamen fatrense were excerpted from already published works and detailed comparison was also made.